2014
DOI: 10.1039/c3dt52632a
|View full text |Cite
|
Sign up to set email alerts
|

Alkali metal derivatives of an ortho-phenylene diamine

Abstract: Treatment of the ortho-phenylene diamine C6H4-1,2-{N(H)Tripp}2 (1, PDAH2, Tripp = 2,4,6-triisopropylphenyl) with two equivalents of MR (M = Li, R = Bu n ; M = Na or K, R = CH2C6H5) afforded the dimetallated alkali metal ortho-phenylene diamide dianion complexes The structure of 2 is monomeric with one lithium coordinated to the two nitrogen centres and the other lithium η 4 -coordinated to the diazabutadiene portion of the PDA scaffold. Similar structural cores are observed for 3 and 4, except that the larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
(93 reference statements)
0
12
0
Order By: Relevance
“…The M–N bond lengths in 3 – 8 (M = Li, Na, K) are all within the expected ranges for enediamide complexes , . The values are primarily determined by the coordination number of the metal and do not change systematically in going from the H2 DAD Dipp to the Me2 DAD Dipp ligand.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…The M–N bond lengths in 3 – 8 (M = Li, Na, K) are all within the expected ranges for enediamide complexes , . The values are primarily determined by the coordination number of the metal and do not change systematically in going from the H2 DAD Dipp to the Me2 DAD Dipp ligand.…”
Section: Resultsmentioning
confidence: 56%
“…For Me2 DAD Dipp , deprotonation of the central methyl groups has been observed in some cases , . Moreover, a number of structurally closely related alkali metal complexes are known, in which the two central carbon atoms of the ligand are part of an additional aromatic system (for instance, derivatives of ortho ‐phenylenediamine) . However, all these complexes have been obtained under different conditions and comprise a variety of solvent co‐ligands, which makes comparison difficult.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the findings on the size dependency of the metal‐site contribution, it was derived that elements in the alkali‐metal group that are bigger in size, such as the radical structures of Cs + and Rb + , would mainly consist of ligand‐centered contributions. Indeed, it was found that radicals of Cs + – and Rb + –diamine complexes adopted a ligand‐centered nature …”
Section: Discussionmentioning
confidence: 99%
“…Although radicals of heavy main elements and transition metals with DAD ligands have received significant interest in the past decades, there are fewer studies on group 1 metal complexes of these ligands . Electron paramagnetic resonance (EPR) spectroscopy is excellently suited for investigating paramagnetic metal complexes and radicals produced in chemical and biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, deprotonation and formation of the corresponding amide has been well‐known since many years. Contrarily to this straight‐forward behavior, N , N ′‐aryl‐substituted 1,2‐diaminobenzene tends to form radical anions especially with the heavier alkali metals rubidium and cesium even with bulky N‐bound 2,6‐diisopropylphenyl substituents 2. This reaction behavior is significantly less expressed for the neopentyl derivative 1 , even though it has been observed for a zincate derivative 3.…”
Section: Introductionmentioning
confidence: 97%